Microstructure evolution of AlSi10Mg alloy in RAP process - Tutuk, Ibrahim; Acar, Serhat; Ozer, Gokhan; Guler, Kerem Altug (WALTER DE GRUYTER GMBH, 2024)
With its computer-aided layer-by-layer production approach, additive manufacturing (AM) and powder bed laser fusion (PBLF) paved the way to produce metallic parts more precisely than any other manufacturing technique. However, the combinability and the interaction of this relatively new manufacturing technique with the other near-net shape production techniques is still a mystery. In this study, the recrystallization and partial melting (RAP) behavior, which is a feedstock production approach for semisolid forming methods, investigated on AlSi10Mg parts produced by PBLF and conventional casting were compared in terms of microstructural and hardness evaluations. After the reheating process, the globalization of Si particles and the breakdown of the Si network around the melt pools were displayed with light microscope and scanning electron microscope (SEM) images. The hardness values of the PBLF as-fabricated specimens were found to be significantly higher than the as-cast specimens; however, the values were almost equaled after the RAP treatment and even got lower on the bottom and top regions of the PBLF samples after 20 min of reheating because of the enlarged shrinkage porosities and the coarsened morphology.
Keywords: additive manufacturing; powder bed laser fusion; AlSi10Mg; recrystallization and partial melting; Materials Science